2017
DOI: 10.1016/j.biomaterials.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage exosomes as natural nanocarriers for protein delivery to inflamed brain

Abstract: Recent work has stimulated interest in the use of exosomes as nanocarriers for delivery of small drugs, RNAs, and proteins to the central nervous system (CNS). To overcome the blood-brain barrier (BBB), exosomes were modified with brain homing peptides that target brain endothelium but likely to increase immune response. Here for the first time we demonstrate that there is no need for such modification to penetrate the BBB in mammals. The naïve macrophage (Mϕ) exosomes can utilize, 1) on the one hand, the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
383
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(401 citation statements)
references
References 67 publications
16
383
2
Order By: Relevance
“…Notably, upregulation of ICAM-1, a common process in inflammation, promoted M/ EVs' uptake by BBB. By means of this, naïve M/ exosomes, after intravenous administration, could cross the BBB and deliver the brain-derived neurotrophic factor (BDNF), into brain (Yuan et al, 2017). Similarly, Haney et al (2015) reported earlier that macrophage-derived exosomes loaded with catalase can be considerably detected in brain of mouse with Parkinson's disease following intranasal administration.…”
Section: Macrophagesmentioning
confidence: 71%
See 1 more Smart Citation
“…Notably, upregulation of ICAM-1, a common process in inflammation, promoted M/ EVs' uptake by BBB. By means of this, naïve M/ exosomes, after intravenous administration, could cross the BBB and deliver the brain-derived neurotrophic factor (BDNF), into brain (Yuan et al, 2017). Similarly, Haney et al (2015) reported earlier that macrophage-derived exosomes loaded with catalase can be considerably detected in brain of mouse with Parkinson's disease following intranasal administration.…”
Section: Macrophagesmentioning
confidence: 71%
“…The naïve macrophage (M/) EVs can penetrate through the BBB in mammals. The mechanism might be that these EVs contain integrin lymphocyte function-associated antigen 1 (LFA-1), intercellular adhesion molecule 1 (ICAM-1) (Jin et al, 2018), and carbohydrate-binding C-type lectin receptors (Aranda-Souza et al, 2019), that can interact with brain vessel endothelial cells comprising the BBB (Yuan et al, 2017). Notably, upregulation of ICAM-1, a common process in inflammation, promoted M/ EVs' uptake by BBB.…”
Section: Macrophagesmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are small phospholipid based nanoparticles decorated with membrane and surface proteins and they are thought to be involved in cell-to-cell transfer of information [16,17]. EVs are currently explored for potential therapy of different applications ranging from cancer therapy [18], inflammation [19], gene delivery [20] and to fighting infections [21] because of their natural composition and inherent targeting properties [22]. Nevertheless, ongoing limitations of EVs include issues of upscale production in a biotechnologically controllable manner and post-processing regarding loading and modification for targeted tissue interaction [23] which may overall compromise their applicability in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature modulation is a common and powerful research strategy to block temperaturedependent processes, such as endocytosis [3842]. While cold-incubation is not specific for a particular mechanism of endocytosis, it is used widely in research community to nonspecifically block all endocytosis.…”
Section: Discussionmentioning
confidence: 99%